Pyridazine and its related compounds: Part 38. Pyrimido[1,2-b]pyridazinone, synthesis and some reactions - Deeb, Ali Abdel Hamid; El-Mariah, Fatma Abdel Rahman; El-Mawgoud, Heba Kamal Abd (European Journal of Chemistry, 2015)
A new method of generating the fused heterocyclic system with bridge head nitrogen pyrimido[1,2-b]pyridazinone, from 3-amino-4,5,6-triphenylpyridazine and malonic acid in presence of phosphoryl chloride is described. The structures of the synthesized compounds were confirmed by their infrared, mass spectrum, 1H NMR and elemental analyses. The antimicrobial activity of the compounds obtained was examined against some selected microorganisms.